Analisis Pengaruh Karakteristik Perusahaan Terhadap Intellectual Capital Disclosure Perusahaan Keuangan Di BEI - Agung Sri Wardhani (Fakultas Ekonomi Universitas Katolik Darma Cendika, 2017)
The purpose of this research is to test the impact level of intellectual capital disclosure on annual financial statements of listed financial companies in Indonesian Stock Exchange. This research has two variables. The first variable is the intellectual capital disclosure as the dependent variable. The second variable is the characteristics of the company (leverage, ownership concentration, type of external auditor, age of listing, independent commissioner, size of the audit committee, and size of the company) as the independent variable. The sample of this research are chosen by using the sampling purposive method. The classic assumption test is used earlier to validate the variables, and the result showed that the variables are valid. The result of this research shows that average rate of intellectual capital disclosure is 37,9%. Multiple regression analysis is used to test the hypothesis. Based on the statistics test result, the independent variable (leverage, ownership concentration, type of external auditor, age of listing, independent commissioner, size of the audit committee, and size of the company) doesn’t have significant effect on intellectual capital disclosure. It concludes that intellectual capital disclosure hasn’t been much revealed on financial companies in Indonesia.